Kepemimpinan Kepala Sekolah Dasar Negeri 14 Rantau Utara Kecamatan Rantau Utara Kabupaten Labuhan Batu - Nini Syafriani Hasibuan; Warjio Warjio; Isnaini Isnaini (Mahesa Research Center, 2022)
This article discusses the analysis of the leadership role of the principal of the 14 Rantau Utara State Elementary School, Rantau Utara District, Labuhan Batu Regency. This type of research is a type of field research (field research) with a qualitative approach. The sources of data for this research are the principal, school teachers in their respective fields, school operators, representatives of several parents. Data collection methods used are observation, interviews and documentation. Then the presentation of the data goes through four stages, namely: data reduction, analyzing data, compiling data and drawing conclusions. The results of this study indicate that, the principal's leadership on school management in terms of the principal's leadership has been fairly effective, in addition to placing himself as a headmaster leader as well as a role model who always provides motivation, direction and advice to students. subordinates both to teachers and staff as well as to their students. Principals in elementary schools maintain order and school discipline, and strive for the progress of the school. In the management of facilities and infrastructure, it is still considered inadequate or not enough because the principal is constrained by funds so that he has not been able to cover the shortcomings in the school, but the principal is still trying to cooperate with the government in the progress and development of the school and can meet the needs of the school. especially in learning.